ZmMBD101 is a DNA binding protein that maintains Mutator elements chromatin in a repressive state in maize - Questa, Julia (2015)
In maize (Zea mays), as well as in other crops, transposable elements (TEs) constitute a great proportion of the genome. Chromatin modifications play a vital role in establishing transposon silencing and perpetuating the acquired repressive state. Nucleosomes associated with TEs are enriched for dimethylation of histone H3 at lysine 9 and 27 (H3K9me2 and H3K27me2, respectively), signals of repressive chromatin. Here we describe a chromatin protein, ZmMBD101, involved in the regulation of Mutator (Mu) genes in maize. ZmMBD101 is localized to the nucleus and contains a methyl-CpG-binding domain (MBD) and a zinc finger CW (CW) domain. Transgenic lines with reduced levels of ZmMBD101 transcript present enhanced induction of Mu genes when plants are irradiated with UV-B. Chromatin immunoprecipitation analysis with H3K9me2 and H3K27me2 antibodies indicated that ZmMBD101 is required to maintain the levels of these histone repressive marks at Mu Terminal Inverted Repeats (TIRs) under UV-B conditions. Although Mutator inactivity is associated with DNA methylation, cytosine methylation at Mu TIRs is not affected in ZmMBD101 deficient plants. Several plant proteins are predicted to share the simple CW-MBD domain architecture present in ZmMBD101. We hypothesize that plant CW-MBD proteins may also function to protect plant genomes from deleterious transposition.